Inferring what hardliners would do: assessing factual knowledge of state policies on immigrant treatment in the US. (2nd October 2018) - Udani, Adriano
ABSTRACT: Survey questions concerning citizenship guidelines, naturalization tests, and party positions largely inform scholarship on policy knowledge of immigration. However, a feature of US immigration enforcement is noticeably absent: the role of state elected officials in making policies on immigrant treatment. Using policy data from the National Council of State Legislature and a nationally representative sample of US voters in the 2014 Cooperative Congressional Election Study (CCES), I validate answers to factual policy questions about whether respondents believe their state enacted three common state policies that affect immigrants: authorizing police to enforce immigration law, offering in-state tuition benefits for undocumented students, and requiring employers to verify the lawful status or citizenship of employees. I find that citizens align their answers to factual immigration policy questions with their predispositions toward immigrants, even if their answers are verifiably incorrect. The results suggest that anti-immigrant citizens seem more knowledgeable of local immigration policies, but only because most state policies on immigrant treatment are restrictive and are consistent with their negative beliefs about immigrants and immigration.